Applying the Skip Navigation Links in the Context of the Websites’ Accessibility of Central Public Administration Bodies in the Banská Bystrica Region - Jana Koprlová (Societas et Iurisprudentia, 2016)
The study focuses in its main aim on seeking yet undetected or undefined deficits in relation to applying the skip navigation mechanism on the websites of the central public administration bodies in the Banská Bystrica Region in the context of improving the websites accessibility and it consists of two separate parts. The first part presents a basic introduction to the questions of skip navigation links, with the key attention paid to the following three main areas: applying of skip navigation links, visual hiding of skip navigation links, and web browsers’ bug related to skip navigation links. The second part of the study concentrates on the basis of analysis of applying the skip navigation links on the websites of the central public administration bodies in the Banská Bystrica Region on the processes focused on detection of potential deficits and gaps in the websites’ accessibility or related possible non-compliance with the legislation in force.